Factors Related to Work-Related Stress in Nurses at The Emergency Department of Naibonat Hospital, Kupang District - Aldy Ratu Edo; Soni Doke; Erny Erawati Pua Upa (Universitas Nusa Cendana, 2022)
Work stress is a stressful feeling or a sense of pressure experienced by employees related to their work. Naibonat Regional General Hospital is a referral health service center in Kupang Regency, East Nusa Tenggara Province. Nurses at the Hospital work for 12 hours/day or 72 hours/week which put them at risk of work-related stress. This study aims to analyze the relationship between age, gender, workload, and years of service with the work stress of nurses. This study was an analytic study with a cross-sectional design. The research was conducted at the Emergency Unit of Naibonat Hospital. Data were collected from September-October 2020. The study population was all nurses, 24 people, working at the Department. All populations are sampled. Hypothesis testing used chi-square with a significance level of 0.05. The results showed that workload (p = 0.000) and work period were associated with stress. Age (p=0.069) and gender (p=1,000) were unassociated with the stress. The Emergency Department of the Hospital needs to pay more attention to the workload of nurses. The workload should be adjusted to the ability and work duties of nurses to avoid failure or mistakes in treating patients and to prevent nurses from having excessive workloads.